2015
DOI: 10.1063/1.4921788
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium shape of nano-cavities in H implanted ZnO

Abstract: showed a similar peak centered at 650 nm. This indicates that the PL and EL processes could be related to the same origin. Even though the center of EL peak was around 650 nm, overall EL peak showed the broad spectrum in the range of 500-850 nm. EL intensity was increased with increasing the forward voltage, as shown in Fig. 4(a). Figure 4(b) shows the light output power of Si NC LED with a SiC film as a function of the forward voltage. Light output power of the Si NC LED was measured from the topside of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In order to identify the facets of the remaining surfaces, the six smooth prismatic side planes of the rods are identified according to K. S. Chen et al [ 23 ]. They used H implantation and subsequent high temperature annealing on ZnO surface to determine the relative surface formation energies and to construct a Wulff plot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the facets of the remaining surfaces, the six smooth prismatic side planes of the rods are identified according to K. S. Chen et al [ 23 ]. They used H implantation and subsequent high temperature annealing on ZnO surface to determine the relative surface formation energies and to construct a Wulff plot.…”
Section: Resultsmentioning
confidence: 99%
“…3g , g' , the 12 tilt surfaces can be divided into six groups belonging to six <1 10> directions. Again K. S. Chen et al [ 23 ] have reported the surface formation energy of ZnO nanowire with zone axis along [1 10]. Their data show that the most stable facets are ( 014) and (10 4).…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al also identified 17 clustering of several (4)(5)(6) VZnVO divacancies from the measured value of PAL in Al irradiated ZnO. Agglomeration of VZn and VO defects (in general (VZn)m (VO)n type with m ≈ n) during annealing (at relatively lower temperature 23 ) or by multiple collision cascades of energetic ions may lead to nano-voids in the system 24,25 . From surface energy consideration, if two open volume defects with similar radii coalesce to a form larger one, energy is lowered roughly by 20%.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the O-terminated internal polar facets are more stable than the Zn-terminated, in agreement with previous observations. 22 This polar facet disappears as the voids grow in size and finally only the semi-polar facets prevail. This is in agreement with calculations showing that the polar planes in ZnO exhibit higher surface formation energy compared to the non-polar planes.…”
mentioning
confidence: 99%